An Investigation of Different Language Choice through Personal Pronouns in the Twitter - Nur Hafiz Abdurahman (Indonesian Journal of EFL and Linguistics, 2017)
This study aimed to find evidence regarding the use of personal pronouns in the discourses produced by males and females. Personal pronouns were chosen as the object of analysis, as several studies has suggested them as one of the features that may distinguish the gender of the authors. This study analysed publically available corpus, Rovereto Twitter N-Gram Corpus (RTC), utilized by Herdagdelen (2013). It is gender-of-the-author tagged, which makes the author’s gender analysis easier. The corpus was analysed using AntConc (Anthony, 2014). From AntConc’s concordance analysis, it was found that women utilised more personal pronouns, especially the ones that can create closer bond. On the other hand, men have greater tendency to distant themselves using generic pronouns than women. In conclusion, men and women in this study may use personal pronouns differently. Keyword: Personal Pronoun, Twitter, AntConc